2018
DOI: 10.1007/s11356-018-2305-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and economic growth: a heterogeneous panel data approach

Abstract: Climate change is a global phenomenon. Its impact on economic growth must therefore be analyzed in accordance with its (time-varying) common effects. We present an econometric analysis that evaluates this effect taking into account its global nature. Contrary to previous evidence that ignores the global effects, we obtain that the rising temperature has not decreased growth in real GDP per capita in the second half of the twentieth century for the world countries. However, we obtain a negative effect of rising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
4
19
0
Order By: Relevance
“…This is because most farming income is generated from these poorer regions, which are also rather dry. This finding was consistent with previous studies, which found that rainfall had positive impacts on the economic growth of poor and arid countries that were reliant on rainfed agriculture (Abidoye and Odusola 2015;Ali 2012;Lanzafame 2014;Miguel and Satyanath 2011;Sequeira et al 2018). In addition, the Mekong River is a major source of water for both northern and northeastern regions.…”
Section: Economic Sector Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is because most farming income is generated from these poorer regions, which are also rather dry. This finding was consistent with previous studies, which found that rainfall had positive impacts on the economic growth of poor and arid countries that were reliant on rainfed agriculture (Abidoye and Odusola 2015;Ali 2012;Lanzafame 2014;Miguel and Satyanath 2011;Sequeira et al 2018). In addition, the Mekong River is a major source of water for both northern and northeastern regions.…”
Section: Economic Sector Resultssupporting
confidence: 92%
“…Lanzafame (2014) also determined that the aggregated effects of rainfall positively influenced economic growth in Africa. Moreover, Sequeira et al (2018) confirmed the positive effect of higher precipitation in poor countries with either hot or temperate climates. Finally, Phatcharopaswatanagul (2018) showed that rainfall had a positive impact on cassava yields in Thailand.…”
Section: Literature Reviewsupporting
confidence: 55%
See 1 more Smart Citation
“…Recent studies explored how rainfall impacted on economic growth and focused on countries with rainfed agriculture. African countries were widely studied with general overall agreement that rainfall positively affected economic growth (Abidoye & Odusola, 2015;Lanzafame, 2014;Miguel et al, 2011;Sequeira et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The climatic variables of temperature and rainfall are often represented in economic growth models within the field of climate change, mostly focused on temperature. The available literatures suggests that increase in temperature has a negative impact on economic growth (Akram, 2012;Lanzafame, 2014;Sequeira, Santos, & Magalhães, 2018) whereas rainfall has both positive (Akram, 2012;Brown, Meeks, Ghile, & Hunu, 2013;Odusola & Abidoye, 2015) and negative impacts on economic growth (Dell, Jones, & Olken, 2012;Tebaldi & Beaudin, 2016). Until recently, few studies have examined and explored how rainfall is related to economic growth, with research conducted mostly in African countries (Ali, 2012;Barrios, Bertinelli, & Strobl, 2010;Berlemann & Wenzel, 2018;Cabral, 2014;Miguel & Satyanath, 2011;Richardson, 2007;Sebastien, 2010) such as Sub-Saharan Africa where rainfed agriculture is dominant (Borgomeo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%